(untitled) (International Conference on Education, Psychology and Humanities, 2026)
The education and legal protection of young athletes has become one of the most urgent scientific and pedagogical issues in the context of contemporary educational reform and the rapid development of sports systems. In modern society, the upbringing of young athletes should be understood as a complex multidimensional process that integrates physical development, psychological stability, moral education, legal awareness, and social adaptation. This issue is of particular relevance under the conditions of globalization, increasing competitiveness in sports, and the growing need to ensure the rights and legitimate interests of minors engaged in professional and amateur sports activities.